Prognostic value of glomerular function estimated by Cockcroft-Gault creatinine clearance, MDRD-4, CKD-EPI and European Kidney Function Consortium equations in patients with acute coronary syndromes - Ndrepepa, Gjin; Holdenrieder, Stefan; Neumann, Franz-Josef; Lahu, Shqipdona; Cassese, Salvatore; Joner, Michael; Xhepa, Erion; Kufner, Sebastian; Wiebe, Jens; Laugwitz, Karl-Ludwig; Gewalt, Senta; Schunkert, Heribert; et al. (Clinica Chimica Acta, 2021)
Background: It remains unknown which equation used to assess the glomerular function is better for risk stratification in patients with acute coronary syndrome (ACS). Methods: This study included 3985 patients with ACS. Glomerular function was assessed using 4 equations: the Cockcroft-Gault creatinine clearance (C-GCrCl), Modification of Diet in Renal Disease-4 (MDRD-4), Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) and European Kidney Function Consortium (EKFC) equations. The primary outcome was one-year all-cause mortality. Results: For each 30 ml/min decrement, the adjusted hazard ratio [HR] with 95% confidence interval [CI] for one-year mortality was 1.67 [1.27–2.25] for C-GCrCl, 1.45 [1.16–1.81] for MDRD-4, 1.76 [1.35–2.30] for CKD-EPI and 1.94 [1.44–2.63] for EKFC equation. Area under the receiver operating characteristic curve (AUC) for one-year mortality was 0.748 [0.709–0.788] for C-GCrCl, 0.670 [0.621–0.718] for estimated glomerular filtration rate (eGFR) calculated by MDRD-4 equation, 0.725 [0.684–0.765] for eGFR calculated by CKD-EPI equation and 0.741 [0.703–0.779] for eGFR calculated by EKFC equation (P = 0.342 for C-GCrCl, vs. EKFC equation and P ≤ 0.009 for all other AUC comparisons). Conclusions: In patients with ACS, C-GCrCl and EKFC equations showed a similar discriminatory power regarding prediction of one-year mortality. Both equations were better than MDRD-4 and CKD-EPI equations for risk discrimination for mortality. Clinical Trial Registration: NCT01944800.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Acute coronary syndrome; Bleeding; Estimated glomerular filtration rate; Mortality; Myocardial infarction